2012
DOI: 10.1371/journal.pone.0050796
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast 26S Proteasome Mutants Are Multi-Drug Resistant Due to Stabilization of the Pap1 Transcription Factor

Abstract: Here we report the result of a genetic screen for mutants resistant to the microtubule poison methyl benzimidazol-2-yl carbamate (MBC) that were also temperature sensitive for growth. In total the isolated mutants were distributed in ten complementation groups. Cloning experiments revealed that most of the mutants were in essential genes encoding various 26S proteasome subunits. We found that the proteasome mutants are multi-drug resistant due to stabilization of the stress-activated transcription factor Pap1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 52 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Oxidative stress is known to activate the stress-activated kinases p38-MAPK and JNK through ASK1 (16,29), and these pathways are known to be induced by proteasome inhibitors (25,65). Further, yeast strains carrying mutations in 26S proteasome subunits overexpress Pap1, the Schizosaccharomyces pombe homolog of the human AP-1 transcription factor (48). We indeed found activation of both p38-MAPK and JNK by b-AP15.…”
Section: Discussionmentioning
confidence: 52%
“…Oxidative stress is known to activate the stress-activated kinases p38-MAPK and JNK through ASK1 (16,29), and these pathways are known to be induced by proteasome inhibitors (25,65). Further, yeast strains carrying mutations in 26S proteasome subunits overexpress Pap1, the Schizosaccharomyces pombe homolog of the human AP-1 transcription factor (48). We indeed found activation of both p38-MAPK and JNK by b-AP15.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, it has been demonstrated that the stabilisation of Pap1 in proteasome mutants of Schizosaccharomyces pombe increases resistance to oxidative stress [43]. We can generalise the idea that the proteasome may play a negative role in the stress response pathways that have transcription regulators as proteasome substrates.…”
Section: Discussionmentioning
confidence: 92%
“…The ubiquitylation of Sec3-913-V5 was determined by precipitating His 6 -ubiquitin under denaturing conditions (in 8 M urea), followed by electrophoresis and blotting for the V5 tag on Sec3-913 as described previously (80).…”
Section: Ubiquitylation Of Sec3-913mentioning
confidence: 99%